Brazilian port reform: An analysis of investments after law nº 12.815/2013 - Igor Ribeiro da Glória; Lúcio Otávio Seixas Barbosa; Cássio Becacici Esteves Vianna (Cadernos Gestão Pública e Cidadania)
Since the enactment of Law nº 12.815/2013, private agents have been allowed to build ports to mainly exploit it commercially, offering port services to anyone interested in moving cargo. This amendment to the legislation aimed to attract private investment to the sector, reducing Brazil’s existing port infrastructure deficit. This work evaluated private investments carried out during the period from 2013 to 2021 in port facilities after the new regulatory framework. The methodology was based on descriptive data analysis, using information from the regulatory agency’s administrative processes authorizing investment in port terminals. The results indicated that investments were focused especially in places where barriers to entry were lower, such as on the banks of inland waterways or, in the case of maritime facilities, where there was already waterway infrastructure managed by some public Port Authorities.